RIG-I like receptor sensing of host RNAs facilitates the cell-intrinsic immune response to KSHV infection - Yang Zhao (Nature Portfolio, 2018)
RIG-I and MDA5, are cytosolic restriction factors and receptors for RNA viruses. Here the authors show during KSHV lytic infection that substrates for recognition by RIG-I and MDA5 are misprocessed RNAs derived from noncoding host RNA molecules, suggesting antiviral immunity can be engaged by sensing of misprocessed cellular RNAs.